Three-year survival of class II restorations using two restorative materials - Molina, Gustavo Fabián (2020)
Fil: Molina, Gustavo Fabían. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Materiales Dentales; Argentina.